2021
DOI: 10.3390/ma14051287
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F-127/Silk Fibroin for Enhanced Mechanical Property and Sustained Release Drug for Tissue Engineering Biomaterial

Abstract: Herein, an injectable thermosensitive hydrogel was developed for a drug and cellular delivery system. The composite was prepared by facile physical mixing of pluronic F-127 (PF) and silk fibroin (SF) in an aqueous solution. The chemical structure, transparency, viscosity, injectability, degradation kinetic, cumulative release of dexamethasone (Dex), a type of corticosteroid drug, and size distribution of the fabricated hydrogels were characterized. Cytotoxicity of the hydrogels was also studied to verify the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Bands around ~1430-1100 cm −1 are observed, which In addition, bands associated with the carbonyl groups (-COOH) ~1725-1700 cm −1 are observed and attributed to the stretching bond of the lutetium acetate precursor employed, and are completely removed at 600 • C, which is an indicator of the moment of the beginning of crystallization process [8]. Bands around ~1430-1100 cm −1 are observed, which correspond to the symmetric and asymmetric vibrations of the C-H bonds, probably from the use of Pluronic F-127; however, as can be observed, they disappear at 700 • C [35,36]. Next, at 500 • C, bands related to the crystallization of LuVO 4 can be observed at ~810-830 cm −1 and ~446-455 cm −1 , which correspond to the V-O bonds of the vanadate group (VO 2 3− ) and Lu-O, respectively [2].…”
Section: Chemical Evolution and Structural Propertiesmentioning
confidence: 73%
“…Bands around ~1430-1100 cm −1 are observed, which In addition, bands associated with the carbonyl groups (-COOH) ~1725-1700 cm −1 are observed and attributed to the stretching bond of the lutetium acetate precursor employed, and are completely removed at 600 • C, which is an indicator of the moment of the beginning of crystallization process [8]. Bands around ~1430-1100 cm −1 are observed, which correspond to the symmetric and asymmetric vibrations of the C-H bonds, probably from the use of Pluronic F-127; however, as can be observed, they disappear at 700 • C [35,36]. Next, at 500 • C, bands related to the crystallization of LuVO 4 can be observed at ~810-830 cm −1 and ~446-455 cm −1 , which correspond to the V-O bonds of the vanadate group (VO 2 3− ) and Lu-O, respectively [2].…”
Section: Chemical Evolution and Structural Propertiesmentioning
confidence: 73%
“…The use of surfactants was also found to induce the self-assembly of fibroin molecules in solution. 92 Wu et al used sodium dodecyl sulfate (SDS) as a gelling agent to produce fibroin hydrogels. 93 It was found that the gelation can be induced by SDS in minutes, based on hydrophobic interactions and electrostatic effects (Figure 6).…”
Section: Surfactant-inducedmentioning
confidence: 99%
“…However, this does not necessarily lead to bad results. Some scholars have concluded that the addition of SF can enable the rapid release of hydrophobic drugs, providing a new technical means for the rapid increase in local drug concentration in some diseases [ 51 ]. Other studies have shown that adjusting SF and other drugs/polymers ratios can lead to sustained-release capabilities of risperidone.…”
Section: Pathophysiological Mechanisms Of Sf Hydrogelsmentioning
confidence: 99%